Shaping life : genes, embryos, and evolution - Maynard Smith, John, 1920- (New Haven, Ct. : Yale University Press, 1998)
Provides a brief account of the progress that is being made in the field of developmental biology, and looks at the ideological differences between the reductionist and holistic views of such scientific advances.
Development : the recent revolution -- The conservation of signals -- Genetic instructions -- Information of self-organization? -- Reductionists to the right, holists to the left.
Originally published: London : Weidenfeld & Nicolson, 1998.
Includes bibliographical references.
Booklist.
Adult
Keywords: Adaptation (Biology); Developmental genetics; Adaptation (Biology); Genetics